Efek Xilooligosakarida (XOS) dalam Mencegah Diabetes Mellitus Tipe 2 - Dwita, Lusi Putri; Rahmi, Hanifah (UI Scholars Hub, 2019)
Type 2 diabetes mellitus (T2DM) is one of the leading causes of death in Indonesia. Early intervention is very important to delay the development of this disease. This study aimed to determine the effect of XOS (Xylo-oligosaccharide) as prebiotic in preventing insulin resistance. The rats were divided into 5 groups: XOS 2 gr/kg, XOS 1 gr/kg, XOS 0.5 gr/kg, diabetic control, and non-diabetic control. Animals were given the test substances and standard feed for 2 weeks then induced with STZ (streptozotocin) except for non-diabetic control. On the 19th day, the data was collected. The results showed that XOS 2 gr/kg BW could prevent blood sugar elevation which is 57.84% lower than diabetic control and show a comparable cholesterol level to normal control. It can be concluded that administration of XOS showed a significant effect in preventing T2DM.